HUBUNGAN STADIUM KLINIS DENGAN DERAJAT DIFERENSIASI SEL PADA PASIEN KARSINOMA SEL SKUAMOSA SERVIKS UTERI DI RSUD. ABDUL MOELOEK BANDAR LAMPUNG - Siti Rowiyah Nur Latifah (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2019)
ABSTRACT: INFLUENCE THE HEAD NURSE SUPERVISION TO NURSING CARE DOCUMENTATION INPATIENT WARD AT PERTAMINA BINTANG AMIN HOSPITAL PROVINCE OF LAMPUNG, INDONESIA Background: The nursing care process related to the professional practice of nursing. Every single step of the nursing care process are complete when it is documented. The controlling of nursing documentation is the important thing, one of controls in nursing management is supervision.Purpose: Knowing that relationship the head nurse supervision with nursing care documentation inpatient ward at Pertamina Bintang Amin Hospital Province of Lampung, Indonesia.Method : It was a quantitive research with analytic survey design and with cross sectional approached. This study used total sampling with the population were all nurses staff inpatient ward which amount to 33 nurses. Data analysis was used Chi Square statistic test.Result: The frequency distribution supervision of head room of 33 respondents surveyed, 15 (45.5%) of respondents said better supervision, and 18 (54.5%) of respondents said poor supervision. Respondents with good nursing care documentation by 20 (60.6%) persons, whereas respondents with poor documentation of nursing care were 13 (39.4%) people, with p-value 0,015.Conclusion: There was influence between head nurse supervision to nursing care documentation inpatient ward at Pertamina Bintang Amin Hospital Province of Lampung, Indonesia. It is expected to the hospital management to be able to further analyze of the nurse's perception on the head nurse supervision and to procesed appropriate policy in order to complete nursing care documentation. Keywords : Head nurse, documentation, supervision